High Doses of Daunorubicin during Induction Therapy of Newly Diagnosed Acute Myeloid Leukemia: A Systematic Review and Meta-Analysis of Prospective Clinical Trials. - Qiang Gong; Lixin Zhou; Shuangnian Xu; Xi Li; Yunding Zou; Jieping Chen (PLoS ONE, 2015)
The right dose of daunorubicin (DNR) for the treatment of newly diagnosed acute myeloid leukemia (AML) is uncertain. Previous trials have shown conflicting results concerning the efficacy of high or low doses of daunorubicin to induction chemotherapy for newly diagnosed AML. A systematic review and meta-analysis was conducted to resolve this controversial issue. We compared the efficacy and safety of high doses of daunorubicin (HD-DNR) and traditional low doses of daunorubicin (LD-DNR) or idarubicin (IDA) during induction therapy of newly diagnosed AML. Data of 3,824 patients from 1,796 articles in the literature were retrieved and six randomized controlled trials were analyzed. The primary outcomes were overall survival (OS), disease-free survival (DFS), and event-free survival (EFS). The secondary outcomes included complete remission (CR), relapse, and toxicity. The meta-analysis results suggest that comparing HD-DNR with LD-DNR, there were significant differences in CR (RR = 1.19, 95%CI[1.12,1.18], p<0.00001), OS(HR = 0.88, 95%CI[0.79,0.99], p = 0.002), and EFS (HR = 0.86, 95%CI [0.74, 1.00], p = 0.008), but not in DFS, relapse, and toxicity. There were no statistically significant differences in any other outcomes between HD-DNR and IDA. The analysis indicates that compared with LD-DNR, HD-DNR can significantly improve CR, OS and EFS but not DFS, and did not increase occurrence of relapse and toxicity.